Cellulose Phosphate From Oil Palm Biomass As Potential Biomaterial - Mohamad Kassim, Mohamad Haafiz (2011)
OPEFB-CP with a DS of 2.4 was synthesized from oil palm biomass via the phosphorylation of microcrystalline cellulose (OPEFB-MCC) using the H3POJ P20sl Et3POJ hexanol method.